"The Land of our Origin": Music and History in the Norway-Azerbaijan Connection. (6th December 2016) - Solomon, Thomas
Abstract : In 1995 Norwegian archaeologist and adventurer Thor Heyerdahl went public with his theory that Scandinavia had been populated by people who had, in the distant past, migrated from present-day Azerbaijan in the Caucasus (Heyerdahl 1995). While academic archaeologists and historians scoffed at Heyerdahl's theories and dismissed them as pseudoscience, the idea that there was an ancient connection between Azerbaijan and Norway, and that the people living in those two nations today might have common ancestors, captured the imaginations of people in both countries. Despite being dismissed by the academic scientific community, Heyerdahl's theories became a source of inspiration for artists, especially musicians. Heyerdahl's speculative approach to research may not have conformed to accepted methodologies for the scientific study of history, but musicians found in Heyerdahl's theories a fruitful point of departure for exploring their purported common past through collaborative artistic projects that prioritized collective creativity based in a common historical imagination. In effect, Heyerdahl's theories became the basis for ways of doing and aestheticizing history through musical practice where the standard for success was based on the production not of verifiable facts, but of aesthetic experiences. This paper provides an account of two of these initiatives. But first I offer some brief remarks on the nature of history, and then a quick overview of Heyerdahl's theories and their critiques.